Detection of Alternaria alternata Associated with Discolored Black Oat Seeds in Korea - Ji-Min Choi; Ji-Hye Song; Joonseob Ahn; Dea-Wook Kim; Kwang-Yeol Yang (Research in Plant Disease, 2023)
In 2023, a number of seeds suspected to be discolored black oat seeds on oat farms in Gangjin were observed and examined for fungal infection. The species Alternaria alternata was predominant, accounting for 84% of all fungal infections. The appearance and quality of seeds harvested in 2022 were compared with seeds harvested in 2023 from the same field. The lightness value was lower in the seeds harvested in 2023, while the electrical conductivity was higher in the seeds harvested in 2023. The content of avenanthramide was found to be 10 times higher in the 2023 seeds than in those harvested in 2022. The accumulated precipitation in Gangjin in May 2023 was 230 times higher than that in May 2022, and the average relative humidity was high. These conditions created an environment suitable for infection of A. alternata, which were thought to have caused discolored black oat seeds.